Land Use Changes in Jeli, Kelantan - Muhammad Firdaus Abdul Karim (2013)
In this thesis, a study on land use change pattern in Jell is been given a focus as part of tool for land planning and development. Land use change pattern can be obtained via spatial analysis using Geographical Information System (GIS) and acquiring satellite imagery in remote sensing. Satellite imagery are pre-processed in geometric correction and further processed in subsetting, masking cloud and supervised classification. Land use maps from supervised classification of satellite imagery and existing land use maps are then digitized into shapefile (.shp) format in ArcGIS software, spatial reference is updated to WGS1984 and accuracy assessment is performed to validate data. Land use change percentage and urban land expansion index (SI) are selected algorithm in this study. The overall accuracy assessment ranged from 61.39% to 92.05% which is moderate to accurate. This study has shown a decrease in forest area, increase in agricultural area as well as urban development. A drastic drop in the virgin forest has also been detected as exploitation of this natural resources takes place upon development and improvement of infrastructure and utilities in Jeli. The highest dropped in forest area was in 2004 with a decrease of -0.76% from the year before. Correlation analysis using Pearson Correlation discovered that there is strong negative correlation between forest and agricultural areas which reflect that with increasing agriculture area forest reserve depletes. The urban expansion index of Jeli showed a low to rapid growth in 1994 and 1997 to 2012 respectively. The study reflected the progressive development in Jeli promotes sustainable usage of forest area when effort to retreat and restore forest was carried out forming a co-existence land use category between forest and agriculture.